Pengembangan E-Modul Berbasis Stem Materi Sistem Pencernaan Manusia Terintegrasi Ayat-Ayat Al-Qur’an Kelas XI SMA - SAL, Sumayyah; Sari Tambunan, Efrida Pima; Khairuna, Khairuna (Universitas Islam Jember, 2024)
This research aims to find out whether a STEM-based e-model with integrated digestive system material on Al-Quran verses is feasible, practical and effective in the learning process. This research uses research and development (R&D) research methods with the 4D model (Define, design development and disseminate). The instruments used in this research were interview sheets, validation sheets for material experts, media experts and experts in integrating Al-Quran verses, questionnaires and tests. The results of this research show that the STEM-based module on integrated digestive system material with Al-Quran verses that has been developed has validity in the material aspect, getting a percentage of 98.14%, in the media aspect, getting a percentage of 96.55%. The practicality module was obtained from the teacher response questionnaire. The practicality of the teacher response questionnaire obtained a percentage of 100% and the practicality of the student questionnaire obtained a percentage of 97.84%. The effectiveness of the pretest and posttest results obtained an N-Gain value of 0.91 with a percentage of 91%. With these results, the module is declared suitable for use. Thus, it is hoped that in the future the module can be used in future learning and research